2019
DOI: 10.3390/ijms20133140
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Epigenetic Mechanisms of Gene Expression in the Pathologies of Hyperhomocysteinemia

Abstract: Hyperhomocysteinemia (HHcy) exerts a wide range of biological effects and is associated with a number of diseases, including cardiovascular disease, dementia, neural tube defects, and cancer. Although mechanisms of HHcy toxicity are not fully uncovered, there has been a significant progress in their understanding. The picture emerging from the studies of homocysteine (Hcy) metabolism and pathophysiology is a complex one, as Hcy and its metabolites affect biomolecules and processes in a tissue- and sex-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 201 publications
1
60
0
2
Order By: Relevance
“…It has been shown that HHcy is associated with a parallel increase in SAH and a decrease in methylation capacity resulting in hypomethylation of DNA [ 15 , 93 ]. Hcy-mediated hypomethylation of DNA and histone modifications impair epigenetic control of gene expression and may contribute to pathogenesis of various HHcy-related human diseases [ 18 ]. Recent comprehensive data mining analyses in human and mouse tissues revealed that 15 nuclear-encoded genes for ETC complex proteins are suppressed in HHcy [ 94 ].…”
Section: Homocysteine and Mitochondrial Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that HHcy is associated with a parallel increase in SAH and a decrease in methylation capacity resulting in hypomethylation of DNA [ 15 , 93 ]. Hcy-mediated hypomethylation of DNA and histone modifications impair epigenetic control of gene expression and may contribute to pathogenesis of various HHcy-related human diseases [ 18 ]. Recent comprehensive data mining analyses in human and mouse tissues revealed that 15 nuclear-encoded genes for ETC complex proteins are suppressed in HHcy [ 94 ].…”
Section: Homocysteine and Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Several mechanisms have been suggested for Hcy-induced oxidative stress, including (i) direct ROS formation via autooxidation in the presence of transition metals, (ii) activation of oxidant systems, and (iii) inhibition of antioxidant systems [ 15 , 16 , 17 ]. Impairment of epigenetic control mechanisms of gene expression, such as DNA methylation, histone modification, and non-coding RNA, is another possible mechanism of Hcy toxicity [ 18 ]. Beyond this, Hcy can change structure and function of proteins by binding to their lysine or cysteine residues; these post-translational modifications (PTMs) are known as N- and S-homocysteinylation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that hHcy promotes neuronal tissue breakdown, oedema and/or cell lysis, or a shift from oxidative energy metabolism toward anaerobic glycolysis due to the mitochondrial dysfunction of [32] which significantly might affect metabolite ratio [5,6,33]. In addition, Met-Hcy cycle is connected to one carbon metabolism and editing processes in proteosynthesis and thus Hcy and its metabolites might interfere with the epigenetic control of gene expression as one of the underlying pathological factors [34].…”
Section: Metabolic and Volumetric Changes In The Hippocampus After Mementioning
confidence: 99%
“…Furthermore, we confirmed previous findings obtained in a cohort of 100 Alzheimer's disease individuals and matched controls, showing that elevated plasma Hcy levels in the AD subjects were linked to reduced methylation levels of several genes in blood DNA, including DNMT1 [14]. Homocysteine is a metabolite for methionine production, and methionine is the precursor of SAM that serves as the universal one-carbon donor for DNA methylation reactions (Figure 1), such that hyperhomocysteinemia (HHcy) is often linked to reduced DNA methylation potential [23], and the epigenetic dysregulation of gene expression is a pathogenic consequence of HHcy in many human diseases [24]. In this context, previous in vitro studies revealed that Hcy treatment altered the expression levels of DNMT1, leading to global or gene-specific DNA methylation changes [25][26][27].…”
Section: Discussionmentioning
confidence: 99%